Surgical management of biliary fistula following associating liver partition and portal vein ligation for staged hepatectomy in pediatric hepatoblastoma: a case report and literature review - Shen, Gang; Zhai, Yunpeng; Zhao, Huashan; Guo, Rui; Xu, Hongxiu; Huang, Sai; Zhang, Shisong (Frontiers in Oncology, 2025)
ObjectiveTo report the clinical data of a pediatric patient with massive hepatoblastoma who underwent associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) following chemotherapy.Case presentationA 1-year-and-8-month-old male infant was diagnosed prenatally with an intrahepatic mass, which was later confirmed as hepatoblastoma via ultrasound-guided biopsy postnatally. The parents declined surgical intervention, leading to voluntary discharge. The child received oral lenvatinib therapy externally, but the tumor continued to enlarge (13.1cm × 7.9cm × 9.9cm), prompting hospital admission. Four cycles of C5VD chemotherapy (cisplatin + vincristine + 5-fluorouracil) were administered, resulting in limited tumor reduction (11.3cm × 5.6cm × 10.8cm). Minimal shrinkage was observed after the fourth cycle compared to the second, with significant intratumoral calcification, suggesting suboptimal further chemotherapeutic efficacy. Surgical intervention was thus decided. Preoperative assessment indicated that direct tumor resection would leave only 24% of the future liver remnant, posing a high risk of liver failure. ALPPS was consequently selected. During the first stage (February 25, 2025), liver partition and right portal vein ligation were performed. Ten days postoperatively, FLR increased to 35%, enabling the second-stage tumor resection (March 9, 2025). Postoperative biliary fistula developed at the liver transection plane and failed conservative management, necessitating a third procedure (hepaticojejunostomy via Roux-en-Y anastomosis) for successful biliary-enteric drainage reconstruction. Adjuvant chemotherapy was continued postoperatively, with no recurrence observed during follow-up.ConclusionALPPS is a safe and effective surgical approach for pediatric patients with massive hepatoblastoma requiring extensive resection and presenting with insufficient FLR.